Seroprevalence of bovine Herpesvirus-1, bovine viral diarrhoea virus, Neospora caninum and Coxiella burnetii in dairy cows in Ethiopia - Gebrerufael Girmay; Bezina Arega Emeru; Desiye Tesfaye Tegegne; Shelema Kelbesa Bora; Workitu Firomsa Gudeta; Betelhem Seyoum Dersso; Beksisa Urge Hurrisa; Gebremeskel Mamu Werid; Shimels Tikuye Yalew; Yohannes Equar Messele (BMC Research Notes)
Abstract Background The reproductive problem is an animal health-related bottleneck that constrains livestock genetic improvement efforts in tropical countries such as Ethiopia. The infectious causes of reproductive disorders are one cause of decreased reproductive efficiency. This study aimed to determine the seroprevalence to Bovine Herpesvirus-1 (BHV1), Bovine Viral Diarrhea Virus (BVDV), Neospora caninum (N. caninum) and C. burnetii (C. burnetii) exposures in dairy cows with reproductive disorders in selected areas of Ethiopia. Overall, 164 serum samples were collected from October 2018 to May 2019 from animals with a history of reproductive disorders. The collected sera were tested for antibody titers to Brucella species, N. caninum, BVDV, BHV1, C. burnetii and Chlamydophila abortus (C. abortus) using Rose Bengal and ELISA. Results The apparent seroprevalence of BHV1, BVDV, N. caninum and C. burnetii were 61%, 33.5%, 4.9% and 0.6%, respectively. Among the selected study areas, the mean apparent seroprevalence was significantly greater in Bishoftu (35.9%), Holeta (34.2%) and Adaberga (28.6%) than in Mekelle (9.9%) and Ambo (16.2%). Among the specific seroprevalence in specific areas, BHV1 was the most common in Adaberga, with an apparent seroprevalence of 92.9%. Similarly, the seroprevalence of BVDV was the highest in Holeta, with an apparent seroprevalence of 73.3%. On the other hand, no seropositive animal to Brucella spp. or C. abortus was found in these study areas. Conclusion BVDV and BHV1 seroprevalence was higher in dairy cattle with a history of reproductive disorder in Ethiopia as compared to the seroprevalence of N. caninum and C. burnetii.